Risk Factors For Contrast Induced Nephropathy in Surgical Intensive Care Unit Patients - Coşkun Araz; Hakan Musa Ayas; Aynur Camkıran; Arash Pirat; Pınar Zeyneloğlu; Gülnaz Arslan (Türk Yoğun Bakim Derneği Dergisi, 2012)
Objective: The aim of this study was to evaluate the risk factors for the development of contrast induced nephropathy (CIN) in surgical intensive care unit (ICU) patients. Material and Method: The charts of the patients who were admitted to the ICU between January 2001 and September 2006 were reviewed. Those patients who were exposed to contrast media (CM) during their ICU stay were included. Patients who were receiving renal replacement therapy at the time of CM exposure were excluded. Patients were divided into two groups based on whether they developed CIN (CIN(+)) or not (CIN(-). CIN was defined as an increase in serum creatinine values of ≥0.5 mg/dl or a ≥25% increase from baseline within 72 hours after administration of contrast agent. Results: Of 42 patients who were included in the study 17 fulfilled the criteria of CIN. There was no statistically significant difference between Group CIN(+) (n=17) and Group CIN(-) (n=25) in terms of demographic features, APACHE II scores, and reasons for ICU admission. Patients in group CIN(+) had a significantly higher rate of congestive heart failure than those in Group (CIN(-) (35% vs 8%, p=0.045). Compared with Group (CIN(-), hemoglobin level before CM exposure as well as partial arterial oxygen pressure and diastolic blood pressure after CM exposure were significantly lower in Group (CIN(+) (12.7±2.5 vs 11.1±1.3 g/dl, 91±21 vs 66±11 mmHg, and 59±17 vs 72±19 mmHg, respectively). Multivariate logistic regression revealed that only partial arterial oxygen pressure was significantly associated with CIN (OR:0.842; CI=0.75–0.95; p=0.005). Conclusion: Our results indicate that a low arterial oxygen pressure is a risk factor for development of CIN in ICU patients. Measures to improve oxygenation may reduce the risk of this complication in ICU patients. (Journal of the Turkish Society Intensive Care 2012; 10: 1-7)